Structural characterisation of spintronic GaMnAs and GaMnN heterostructures grown by molecular beam epitaxy - Fay, Mike W.; Han, Y.; Novikov, Sergei V.; Edmonds, K.W.; Wang, K.; Gallagher, B.L.; Campion, R.P.; Foxon, C.T.; Brown, Paul D. (Springer-Verlag, 2005)
Observations of orthogonal orientations demonstrate the development of banded contrast features on inclined {-1-1-1}B planes for the [110] projection within micron thick samples, attributed to a compositional fluctuation in the Mn content. The relationship of Mn content and layer critical thickness for the onset of precipitate and stacking fault formation is investigated. The formation of a Mn-O layer at the surface of the samples is also observed. The growth of GaMnN/(001)GaAs heterostructures with and without AlN/GaN buffer layers is also compared. Layers without buffer layers show MnAs inclusions into the GaAs, with a reduced Mn content of the GaMnN layer significantly below the nominal composition. The use of AlN/GaN buffer layers is found to greatly reduce the density of these MnAs inclusions, retaining a higher proportion of the Mn within the epilayer.